Open-mindedness and its relationship to personality strength among university students - Thajil, Laila Najem (Journal of Educational and Psychological Sciences, 2025)
The current research aimed to identify open-mindedness among university students and strength of character, as well as the correlation between open-mindedness and strength of character among university students. It is one of the applied researches with a correlational relationship. The method used is descriptive. To achieve the objectives of the research, the researcher adopted the open-mindedness scale and prepared the strength of character scale, which consisted of (47) paragraphs for open-mindedness and (20) paragraphs for strength of character. It was applied to a sample of female students in the Kindergarten Department at the College of Education for Girls/ University of Baghdad and the College of Basic Education/ University of Iraq (Kindergarten Department), Imam Al-Kadhim College, for the academic year (2023-2024). The research sample consisted of (200) female students who were selected randomly. After applying the research, the following results were reached: The female students in the Kindergarten Department have open-mindedness and have strength of character. There is a correlation between the two variables, but the percentage is very weak. In light of the results, the researcher put forward a number of recommendations and proposals, including emphasizing the study of positive concepts in university curricula and enhancing them. And adopting it, holding seminars in guidance units to address types of thinking, including open thinking, the necessity of paying attention to the media and emphasizing personality traits and evaluating them, a special educational, cultural, and educational program.
Keywords: open-mindedness; strength of character